Establishment of a TaqMan Quantitative Real-Time PCR for Detecting Lawsonia intracellularis - Zhiqiang Hu; Ranran Lai; Wei Xu; Ran Guan; Zhimin Zhang; Guangwen Yan; Guiying Hao (Veterinary Sciences)
Porcine proliferative enteropathy (PPE) is an infectious disease in pigs, caused by Lawsonia intracellularis (LI), affecting their intestines during growth and finishing stages, leading to higher production costs. Current detection methods for LI face two main challenges, delayed results and high costs, making them impractical for large-scale pig farming epidemiological surveys. This study developed a TaqMan-qPCR method using specific probes and primers based on the LI aspartate ammonia lyase genes from GenBank, completing detection in just 45 min. After optimizing reaction conditions, sensitivity analysis revealed that the detection limit of this method was 4.6 copies/μL targeting standard plasmids. The results of the specificity analysis showed no cross-reactivity with other common porcine pathogens, highlighting its specificity. The inter- and intra-group coefficients of variation were both <1%, indicating high reproducibility. Furthermore, the TaqMan-qPCR demonstrated 100% relative sensitivity, and a 92.50% compliance rate compared to conventional PCR, suggesting it could be a complement to the conventional PCR method. In summary, the TaqMan-qPCR method established in this study is not only suitable for epidemiological investigations and early qualitative and quantitative diagnosis of proliferative enteropathy in pigs, but it is also valuable for studying the biological characteristics of LI.